Prior stress promotes the generalization of contextual fear memories: Involvement of the gabaergic signaling within the basolateral amygdala complex - Bender, Crhistian Luis (2018)
Fear generalization occurs when a response, previously acquired with a threatening stimulus, is transferred to a similar one. However, it could be maladaptive when stimuli that do not represent a real threat are appraised as dangerous, which is a hallmark of several anxiety disorders. Stress exposure is a major risk factor for the occurrence of anxiety disorders and it is well established that it influences different phases of fear memory; nevertheless, its impact on the generalization of contextual fear memories has been less studied. In the present work, we have characterized the impact of acute restraint stress prior to contextual fear conditioning on the generalization of this fear memory, and the role of the GABAergic signaling within the basolateral amygdala complex (BLA) on the stress modulatory effects. We have found that a single stress exposure promoted the generalization of this memory trace to a different context that was well discriminated in unstressed conditioned animals. Moreover, this effect was dependent on the formation of a contextual associative memory and on the testing order (i.e., conditioning context first vs generalization context first). Furthermore, we observed that increasing GABA-A signaling by intra-BLA midazolam administration prior to the stressful session exposure prevented the generalization of fear memory, whereas intra-BLA administration of the GABA-A antagonist (Bicuculline), prior to fear conditioning, induced the generalization of fear memory in unstressed rats. We concluded that stress exposure, prior to contextual fear conditioning, promotes the generalization of fear memory and that the GABAergic transmission within the BLA has a critical role in this phenomenon.